PENGARUH PENINGKATAN DOSIS KALIUM DAN JENIS PESTISIDA NABATI TERHADAP PERSENTASE SERANGAN HAMA DAN PRODUKSI KENTANG DI SUMATERA UTARA - Sidauruk, Lamria; Kaban, Masdasari; Sihombing, Parsaoran (Universitas Medan Area, 2019)
Potato production in Karo and Simalungun Regency of North Sumatra is severely limited by the high number of pest attacks, so that the use of pesticides is absolutely necessary. Increasing potassium doses and application botanical pesticides can be used as a strategy to reduce pest attacks on potatoes. This study aims to determine whether an increase in potassium dose and application of some botanical pesticides can reduce the percentage of pest attacks and then increasing potato production. Research was designed by factorial Randomized Block Design (RBD) with 2 factors, namely Potassium Dosage consist of 4 levels: K0 = Control; K1 = 100 kg / ha (30 g / plot); K2 = 150 kg / ha (45 g / plot); K3 = 200 kg / ha (60 g / plot). And the second factor is the type of botanical pesticide which consist of 3 levels, namely: N1 = 20 g Neem leaves/ liter of water; N2 = 20 g babadotan leaves/ liter of water; N3 = 20 g Kipahit leaves/ liter of water. Data were analyzed by analyzed of variance.The results showed that an increase in potassium dosage did not significantly affect the percentage of pest attacks and plant production variables. Botanical pesticides have a significant effect on the percentage of pest attacks, but have not significant effect on crop production variables. The lowest percentage of pest attacks was obtained from the application of botanical pesticides from babadotan leaf extract. In general, the percentage of pest attacks in the category was very low (<25%), so that not significantly affect to production variables.